2020
DOI: 10.3390/agronomy10091378
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Changes in Thermal, Qualitative, and Antioxidant Properties of Terebinth (Pistacia atlantica) Fruit under Different Drying Methods

Abstract: This study aims to investigate the effect of different drying methods on the thermal, qualitative, and antioxidant properties and pH of terebinth. To perform the experiments in this study, the hot air (HA), infrared (IR), microwave (MW), hot air–infrared (IR–HA), and hot air–microwave drying (MW–HA) methods were considered. The results showed that the minimum drying time was obtained by the hot air–microwave (MW–HA) method. However, the lowest specific energy consumption (SEC) and the highest energy efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…Moreover, it destroyed the product texture and formed channels with larger diameters, thus preventing the surface from hardening, hence accelerating the free water evaporation. D eff will decrease as a result of a decline in the drying time [ 33 ]. Similar results were reported by other researchers for cranberry snacks [ 17 ], blackberry [ 30 ], and okra [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it destroyed the product texture and formed channels with larger diameters, thus preventing the surface from hardening, hence accelerating the free water evaporation. D eff will decrease as a result of a decline in the drying time [ 33 ]. Similar results were reported by other researchers for cranberry snacks [ 17 ], blackberry [ 30 ], and okra [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Szadzińska et al [ 46 ] reported that dried beetroot resulting from microwave–hot-air drying with ultrasonic pretreatment had fewer color changes than drying with the microwave–hot-air, hot-air, and hot-air with ultrasonic pretreatment methods. The infrared–hot-air drying further darkened the color of hawthorn fruit compared to the infrared–hot-air drying with ultrasonic pretreatment, where the dark color after the drying process was due to the fact of chlorophyll degradation [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study are consistent with the results published by other researchers. The energy efficiency values for drying chamomile in hot air dryers ranged between 1.91% and 6.76% [44], for apple slices between 2.87% and 9.11% [46], for Pistacia atlantica in a hot air dryer equal to 5.65% [47], and for peppermint leaves in a hot air dryer with ultrasonic pretreatment varying between 1.41% and 3.69% [12]. Albini et al obtained the drying efficiency and energy efficiency for barley drying in a hot air dryer ranging 8%- Increasing the ultrasonic radiation time from 0 (control sample) to 30 min significantly decreased the SEC (p < 0.05), because with increasing the ultrasonic pretreatment time, the product texture is more destroyed and the hard layer does not form in the product during the drying process, and thus, the product dries faster, and consequently, the SEC in the dryer is reduced [45].…”
Section: Energy Efficiency and Drying Efficiencymentioning
confidence: 99%
“…The results of this study are consistent with the results published by other researchers. The energy efficiency values for drying chamomile in hot air dryers ranged between 1.91% and 6.76% [44], for apple slices between 2.87% and 9.11% [46], for Pistacia atlantica in a hot air dryer equal to 5.65% [47], and for peppermint leaves in a hot air dryer with ultrasonic pretreatment varying between 1.41% and 3.69% [12]. Albini et al obtained the drying efficiency and energy efficiency for barley drying in a hot air dryer ranging 8%-17.4% and 24%-34.2%, respectively [48].…”
Section: Energy Efficiency and Drying Efficiencymentioning
confidence: 99%